1988
DOI: 10.1029/jd093id04p03879
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the stratospheric conductivity and its variation at three latitudes

Abstract: Measurements of the atmospheric conductivity from nine high‐altitude balloon flights are presented. The measurements were obtained between the altitudes of 10 and 30 km at three locations widely separated in latitude, providing the opportunity to investigate conductivity variations on local and global scales. The data contribute to the set of global conductivity measurements, which are generally lacking. The conductivity profiles exhibit a considerable variability from day to day which does not correlate with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
1
20
2
Order By: Relevance
“…Changes in conductivity due to aerosol layers in the stratosphere have been observed by Kondo et al (1982a;1982b); Rosen et al (1985); and Byrne et al (1988) mainly from balloon platforms. Gringel and Muhleisen (1978) measured the number concentration of small particles and conductivity simultaneously from a balloon platform, in which conductivity was found to decrease by ≈11% in a layer in which the particle number concentration was 2000cm -3 above the background value.…”
Section: Aerosol Layersmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in conductivity due to aerosol layers in the stratosphere have been observed by Kondo et al (1982a;1982b); Rosen et al (1985); and Byrne et al (1988) mainly from balloon platforms. Gringel and Muhleisen (1978) measured the number concentration of small particles and conductivity simultaneously from a balloon platform, in which conductivity was found to decrease by ≈11% in a layer in which the particle number concentration was 2000cm -3 above the background value.…”
Section: Aerosol Layersmentioning
confidence: 99%
“…Vertical profiles of conductivity have been measured by this method by many investigators including Kellogg and Weed (1968); Hale et al (1968); Mozer and Serlin (1969); Mitchell and Hale (1973); Byrne et al (1988); Hu and Holzworth (1996); Holzworth and Bering (1998) ;Bering et al (2005) and John et al (2009) using free balloons, constant altitude balloons and rockets. The relaxation method is also popular on space missions, as the same probe instrument can be used to determine both conductivity and electric field, thus saving space and power, which is in small supply e.g.…”
Section: Measurement Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus this technique is useful only for altitudes above 10 km. An extensive discussion of the expected response of the probes and the methods used to obtain the conductivity data can be found in Byrne et al (1988Byrne et al ( , 1990Byrne et al ( , 1991.…”
Section: Instrumentationmentioning
confidence: 99%
“…In previous publications (Byrne et al, 1988(Byrne et al, , 1991Bering et al, 2003), we investigated these and other effects extensively with regard to their effects on our conductivity data from the earlier flights (prior to 1987). In our most recent survey paper, it was suggested that there may be a latitude gradient in the natural variance of stratospheric conductivity (Bering et al, 2003).…”
Section: Introductionmentioning
confidence: 97%